2006
DOI: 10.1002/elps.200600346
|View full text |Cite
|
Sign up to set email alerts
|

ITP in dynamically double‐coated fused‐silica capillaries

Abstract: Bidirectional ITP in fused-silica capillaries double-coated with Polybrene and poly-(vinylsulfonate) is a robust approach for analysis of low-molecular-mass compounds. EOF towards the cathode is strong (mobility >4.0 x 10(-8) m(2)/Vs) within the entire pH range investigated (2.40-8.08), dependent on ionic strength and buffer used and, at constant ionic strength, higher at alkaline pH. Electrokinetic separations and transport in such coated capillaries can be described with a dynamic computer model which permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…The same was found to be true for the prediction of ITP in PMMA capillaries [129]. Furthermore, recent work by Caslavska and Thormann revealed that fused-silica capillaries double coated with Polybrene and poly(vinylsulfonate) feature a strong cathodic EOF across the entire pH range such that bidirectional ITP zone patterns at acidic pH reach the detector without the addition of imposed flow [153].…”
Section: Aspects Of Itp and Mbesupporting
confidence: 62%
“…The same was found to be true for the prediction of ITP in PMMA capillaries [129]. Furthermore, recent work by Caslavska and Thormann revealed that fused-silica capillaries double coated with Polybrene and poly(vinylsulfonate) feature a strong cathodic EOF across the entire pH range such that bidirectional ITP zone patterns at acidic pH reach the detector without the addition of imposed flow [153].…”
Section: Aspects Of Itp and Mbesupporting
confidence: 62%
“…This was divided into 20 000 equal segments with a constant voltage of 2500 V (500 V/ cm, the equivalent field strength used by Sueyoshi et À9 m 2 /Vs) was set using the model described in Caslavska et al [21]. For clarity, injection and micellar volumes will only be discussed relative to the 25-mm capillary length.…”
Section: Methodsmentioning
confidence: 99%
“…For measuring the low EOF and the imposed flow generated via application of pressure during electrophoresis in an LPA coated capillary, a setup with a C 4 D as described elsewhere was employed. Briefly, it comprised a PrinCE sampler (model 560, Prince Technologies, Emmen, The Netherlands), a 50 μm id capillary of 90 cm total length and the detector at 47 % of capillary length.…”
Section: Methodsmentioning
confidence: 99%
“…GENTRANS permits the combined simulation of the temporal behavior of electrophoresis and electroosmosis under constant voltage or current conditions and was previously used to estimate the pH and ionic strength dependent EOF in uncoated fused‐silica and polymethylmethacrylate (PMMA) capillaries . In another effort, the pH independent EOF in dynamically double coated fused‐silica capillaries featuring a charged surface was studied in the same way . Furthermore, this dynamic CE model which uses material or surface property specific input data for estimation of electroosmosis was applied to investigate fundamental aspects of isoelectric focusing in capillaries or microchannels made from bare fused‐silica, fused‐silica coated with a sulfonated polymer, PMMA and poly(dimethylsiloxane) .…”
Section: Introductionmentioning
confidence: 99%